Effects of vitamin E, pentoxifylline and aprotinin on light-induced retinal injury - Yilmaz, Turgut; Aydemir, Orhan; Ozercan, Ibrahim H.; Ustundag, Bilal (Karger, 2007)
Purpose: A considerable amount of clinical and experimental evidence exists suggesting the involvement of reactive oxygen species (ROS) in the etiology of light-induced retinal injury. The aim of this study was to investigate the protective role of vitamin E, pentoxifylline (PTX) and aprotinin against light- induced retinal injury in guinea pigs. Methods: Thirty adult male guinea pigs were divided into 5 groups of 6 animals each. The first group was used as control. The guinea pigs were kept in cyclic light for 2 weeks before the experiments. The animals were maintained in 12-hour light- dark cycles, before and after exposure to intense white fluorescent light, for as long as 12 h and then returned to cyclic light. Groups 3-5 received intraperitoneal injections of vitamin E, PTX and aprotinin, respectively. One eye of each animal was selected for histopathological evaluation and the other for biochemical assay. Retinal malondialdehyde ( MDA) levels and the thickness of the outer nuclear layers were measured. Results: The compounds had the following relationships: vitamin E more than PTX more than aprotinin in preventing light- induced retinal damage. All 3 gave significant protection against the formation of MDA. Retinas of all 3 treatment groups had been protected from light- induced injury. Conclusion: The intraperitoneal vitamin E, PTX and aprotinin supplementations may strengthen the antioxidant defense system because of decreased ROS, and these agents may play a role in treating light- induced retinal injury. Copyright (c) 2007 S. Karger AG, Basel.
Keywords: retina; light-induced injury; vitamin E; aprotinin; pentoxifylline